2006
DOI: 10.1159/000090950
|View full text |Cite
|
Sign up to set email alerts
|

Human Placental Lactogen Decreases Regional Blood Flow in Anesthetized Pigs

Abstract: In 22 pigs anesthetized with sodium pentobarbitone, changes in blood flow caused by infusion of human placental lactogen into the left renal, external iliac, and anterior descending coronary arteries were assessed using electromagnetic flowmeters. In 17 pigs, infusion of human placental lactogen whilst keeping the heart rate and arterial pressure constant decreased coronary, renal and iliac flow. In 5 additional pigs, increasing the dose of human placental lactogen produced a dose-related decrease in regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In these experimental conditions, intra-arterial infusion of human placental lactogen caused in each pig of this study a decrease in coronary, renal and iliac blood flow, while intra-arterial infusion of the vehicle at the same rate as that of the human placental lactogen did not cause any changes in the baseline values of the same flows. These results confirm previously reported findings obtained in the same experimental model showing that human placental lactogen causes coronary, renal and iliac vasoconstriction (Grossini et al 2006).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In these experimental conditions, intra-arterial infusion of human placental lactogen caused in each pig of this study a decrease in coronary, renal and iliac blood flow, while intra-arterial infusion of the vehicle at the same rate as that of the human placental lactogen did not cause any changes in the baseline values of the same flows. These results confirm previously reported findings obtained in the same experimental model showing that human placental lactogen causes coronary, renal and iliac vasoconstriction (Grossini et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Human placental lactogen was infused for a period of 5 min into the coronary, renal or iliac arteries at a dose of 0.2 μg for each millilitre per minute of measured blood flow with an infusion pump (Model 22, Harvard Apparatus), working at constant rate of 1 ml min −1 , by using a catheter connected to a butterfly needle inserted into the arteries distal to the flowmeter probes. The dose of hormone to be infused was calculated from its reported rate of secretion in pregnant women of about 1-3 g day −1 (Walker et al 1991) and has been previously demonstrated in the same experimental model to cause coronary, renal and iliac vasoconstriction (Grossini et al 2006). Recordings taken for 10 min during the steady state before each infusion of human placental lactogen were used as controls.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects induced by PL on the vasculature are not fully understood, our data are among the first to suggest the role played by this hormone in the endothelium and in the NO-dependent relaxation of the aorta, a process that may be related to the redistribution of blood flow that occurs during pregnancy [7,54] . It is important to note that the experimental approaches utilized, as well as the conditions under which the experiments were undertaken, are important factors to consider, because the vasoconstrictor effects induced by GH and PL via the inhibition of NO have been reported in other vascular beds and in the setting of other experimental approaches [15,16,18] , findings suggestive of the differential actions of these hormones in different vascular beds. One possible explanation for these differential effects is the presence of the GHR in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence indicates that PRL, GH, and PL induce regional vasoconstriction via the inhibition of NO-mediated vasodilation, a process regulated by the β2-adrenergic receptors in coronary, renal and iliac vessels in anesthetized pigs [15][16][17] . Supporting these findings, another study has demonstrated that transgenic mice overexpressing the bovine GH gene exhibited increased mean arterial blood pressure, an effect associated with decreases in the lumens of the vascular beds of the hindquarters, which resulted in the development of hypertension [18] .…”
Section: Introductionmentioning
confidence: 99%